2020
DOI: 10.3390/nano10010096
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Ag for Cu in Cu2ZnSn(S,Se)4: Toward Wide Band Gap Absorbers with Low Antisite Defects for Thin Film Solar Cells

Abstract: Cation substitution is a promising approach to reduce the antisite defects and further improve the efficiency of Cu2ZnSn(S,Se)4 (CZTSSe) cells. In this paper, silver (Ag) has been introduced into Cu2ZnSn(S,Se)4 (CZTSSe) thin film to replace Cu partially and form (Cu1-xAgx)2ZnSn(S,Se)4 (0 ≤ x ≤ 1) (CAZTSSe) alloy films by combination of solution method and a rapid annealing technique. The fundamental properties of the mixed Ag-Cu kesterite compound are systematically reported as a function of the Ag/(Ag+Cu) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The latter problem is generally believed to originate from band tails caused by Cu-Zn antisite defects [4]. Partial substitution of Cu for Ag is supposed to be a promising approach to reducing the antisite defect density and thus the band tailing [5,6]. Theoretical calculations demonstrated that due to a substantially larger ionic radius of Ag + (1.14 Å) in comparison with Cu + (0.74 Å) or Zn 2+ (0.74 Å), the formation energy of the Ag Zn defect (at 0.2 eV above the valence band edge) is much larger…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem is generally believed to originate from band tails caused by Cu-Zn antisite defects [4]. Partial substitution of Cu for Ag is supposed to be a promising approach to reducing the antisite defect density and thus the band tailing [5,6]. Theoretical calculations demonstrated that due to a substantially larger ionic radius of Ag + (1.14 Å) in comparison with Cu + (0.74 Å) or Zn 2+ (0.74 Å), the formation energy of the Ag Zn defect (at 0.2 eV above the valence band edge) is much larger…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of R S and the improvement of R Sh for the CMZTSSe device are mostly due to the increase of grain size and the decrease of defect density. The decrease in R S and improved R Sh result in the improvement of J SC and FF [ 14 ]. The V OC of CMZTSSe device increases from 356 to 385 mV in comparison with the CZTSSe device.…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of Cd for Zn can significantly increase the PCE of CZTSSe devices from 5.3% to 9.24%, which indicates that cation replacement of Zn has great potential for improving the PCE of CZTSSe solar cells [ 11 , 12 ]. Replacing Cu with Ag in CZTSSe is also an efficacious method to decrease the concentration of anti-site defects, which, thereby, improves device performance [ 13 , 14 , 15 ]. However, the general substitution elements such as Ag and Cd are mostly rare or toxic, which deviates from the profit of CZTSSe.…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem is generally believed to originate from band tails caused by Cu-Zn antisite defects [4]. Partial substitution of Cu for Ag is supposed to be a promising approach to reduce the antisite defect density and thus the band tailing [5,6]. Theoretical calculations demonstrated that due to a substantially larger ionic radius of Ag + (1.14 Å) in comparison with Cu + (0.74 Å) or Zn 2+ (0.74 Å), the formation energy of the AgZn defect (at 0.2 eV above the valence band edge) is much larger than that of the CuZn defect (0.12 eV).…”
Section: Introductionmentioning
confidence: 99%
“…There is a noticeable discrepancy in the literature regarding the dependence of the phonon Raman peak position and width on the Ag content in CAZTS, the NC size, or non-stoichiometry [5,39]. With the growing number of reports on the synthesis and applications of colloidal AZTS NCs [6,9,11,33,40,41], the physics and chemistry of defects and structural phases in such NCs need to be explored.…”
Section: Introductionmentioning
confidence: 99%